Successful dietary changes correlate with weight‐loss outcomes in a new dietary weight‐loss program - Mindy H. Lee; Annabelle Shaffer; Nouf W. Alfouzan; Catherine C. Applegate; Jennie C. Hsu; John W. Erdman Jr; Manabu T. Nakamura (Wiley, 2024)
Abstract Background Currently available behavioral and dietary weight‐loss programs lack magnitude and sustainability compared with bariatric surgery. A novel dietary weight‐loss program was developed to assist participants in achieving sustainable diet changes by building knowledge and skills in food self‐selection. Although the approach worked, a large variation was observed in outcome among participants. Objective Determine factors affecting weight‐loss outcomes among participants to further improve the efficacy of the program. Methods Participants attended 19 dietary educational sessions during a 1‐year intervention which included prescribed homework. Changes in weight, diet, and body composition were assessed. Results Participants (n = 22) achieved mean body weight loss of −6.49(8.37%, p < 0.001) from baseline at 12 months. Nine participants (41%) achieved weight loss >5% of initial bodyweight; two reached a Body Mass Index 25 kg/m2. A large divergence in weight loss among participants was observed; successful (n = 9) achieved −12.9(9.6)% while unsuccessful achieved −2.03(2.78)%. Dietary protein and fiber density by 24‐h records showed a significant and inverse correlation with weight loss (%) throughout the program. Weight loss at 3 months and 12 months showed a strong correlation (r = 0.84). Participants with self‐reported depression lost significantly less weight than those without depression at 12 months (p < 0.03). Conclusions Divergence in weight‐loss outcomes among the participants is likely due to a difference in successful dietary implementation. Intra‐cohort analysis indicates early weight‐loss success and early dietary implementation was predictive of long‐term success.